DRYING OF SLURRIES AND PASTES IN FLUIDIZED BED OF INERT PARTICLES - B. Grbavčić, Ž. (Journal of Engineering & Processing Management, 2009)
A fluid bed dryer with inert particles represents a very attractive alternative to other drying technologies according to the main efficiency criteria, i.e. specific water evaporation rate, specific heat consumption and specific air consumption. A high drying efficiency results from the large contact area and from the large temperature difference between the inlet and outlet air. A rapid mixing of the particles leads to nearly isothermal conditions throughout the bed. A fluid bed dryer with inert particles was used for drying of slurries. Experiments were performed in a cylindrical column 215 mm in diameter with glass spheres as inert particles. The effects of operating conditions on dryer throughput and product quality were investigated. Main performance criteria, i.e. specific water evaporation rate, specific heat consumption and specific air consumption, were quantified. Temperature profile along the bed was mapped, and nearly isothermal conditions were found due to thorough mixing of the particles. The industrial prototype with fluid bed of 0.8 m in diameter and capacity 650 kg of evaporated moisture per hour was realized on the basis of presented investigations on pilot unit. The most important results are 50% decrease in energy consumption and no-additional grinding of dried product in comparison with old tunnel drying technology.